Numerical analysis of heat transfer and fluid flow of a wavy delta winglets in a rectangular duct. (June 2017) - Maithani, Rajesh; Silori, Anshuman; Rana, Jitesh; Chamoli, Sunil
Abstract: In the present investigation, 3-dimensional Computational fluid dynamics (CFD) investigation has been carried out to study the heat transfer and friction characteristics of a solar air heater duct roughened with wavy delta winglets as turbulent promoters. The roughness in the shape of wavy delta winglets had not been investigated previously. The Nusselt number and friction factor characteristics are determined for different value of Reynolds number range between 3000 and 18, 000. Considering the literature, the k-ε turbulence model was used for analysis. The maximum Nusselt number enhancement was found to be 2.23 times over the flat plate using a relative longitudinal pitch of 3 with five wave winglets at Reynolds number of 5000 with an increase in friction factor by 10.3 times. The maximum thermo-hydraulic performance obtained for the configuration was 2.08.